Male and Female Teachers’ Communication Styles in EFL Classroom Interaction: A Discourse Analysis - Rahmaeni, Rahmaeni (Majesty Journal, 2023)
Teachers’ communication styles play an important role in shaping classroom interaction, student participation, and the effectiveness of the teaching and learning process. This study aimed to explore the communication styles used by male and female teachers in EFL classroom interaction, identify the similarities and differences between their communication styles, and examine the aspects influencing those styles. This research employed a qualitative design using a discourse analysis approach. The participants were two male and two female English lecturers from the English Education Department of Universitas Negeri Makassar. Data were collected through classroom observation, video recording, and interviews. Each lecturer was observed and recorded in two meetings, resulting in eight classroom recordings. The recorded interactions were transcribed and analyzed based on four categories of communication styles: assertive, aggressive, passive, and passive-aggressive. The findings revealed that both male and female teachers used all four communication styles in classroom interaction. Assertive style was the most dominant communication style used by both groups, while passive-aggressive style appeared least frequently. Male teachers were more dominant in using assertive, aggressive, and passive styles, whereas female teachers used passive-aggressive style more frequently. The findings also showed that teachers’ communication styles were influenced by classroom atmosphere, teaching time, and subject matter. This study suggests that awareness of communication styles is essential for EFL teachers because appropriate classroom communication can support student engagement, improve interaction, and create a more effective learning environment.